The clue of the velvet mask - Keene, Carolyn (New York, Grosset & Dunlap, 2005)
When a gang that uses parties as a cover for robberies victimizes a masquerade party Nancy is attending, the teen-age detective switches identity with her girl friend to solve the case.
With: Mystery at the ski jump, by Carolyn Keene. New York, Grosset & Dunlap, 1968.
Keywords: Drew, Nancy (Fictitious character) -- Fiction; Detective and mystery stories, American